Peptidylarginine deiminase inhibition disrupts NET formation and protects against kidney, skin and vascular disease in lupus-prone MRL/lpr mice. Issue 12 (7th August 2014) - Knight, Jason S; Subramanian, Venkataraman; O'Dell, Alexander A; Yalavarthi, Srilakshmi; Zhao, Wenpu; Smith, Carolyne K; Hodgin, Jeffrey B; Thompson, Paul R; Kaplan, Mariana J
Abstract : Objectives: An imbalance between neutrophil extracellular trap (NET) formation and degradation has been described in systemic lupus erythematosus (SLE), potentially contributing to autoantigen externalisation, type I interferon synthesis and endothelial damage. We have demonstrated that peptidylarginine deiminase (PAD) inhibition reduces NET formation and protects against lupus-related vascular damage in the New Zealand Mixed model of lupus. However, another strategy for inhibiting NETs—knockout of NOX2 —accelerates lupus in a different murine model, MRL/ lpr . Here, we test the effects of PAD inhibition on MRL/ lpr mice in order to clarify whether some NET inhibitory pathways may be consistently therapeutic across models of SLE. Methods: NET formation and autoantibodies to NETs were characterised in lupus-prone MRL/ lpr mice. MRL/ lpr mice were also treated with two different PAD inhibitors, Cl-amidine and the newly described BB-Cl-amidine. NET formation, endothelial function, interferon signature, nephritis and skin disease were examined in treated mice. Results: Neutrophils from MRL/ lpr mice demonstrate accelerated NET formation compared with controls. MRL/ lpr mice also form autoantibodies to NETs and have evidence of endothelial dysfunction. PAD inhibition markedly improves endothelial function, while downregulating the expression of type I interferon-regulated genes. PAD inhibition also reduces proteinuria and immune complex deposition in the kidneys, while protecting against skin disease. Conclusions: PAD inhibition reduces NET formation, while protecting against lupus-related damage to the vasculature, kidneys and skin in various lupus models. The strategy by which NETs are inhibited will have to be carefully considered if human studies are to be undertaken.